2019
DOI: 10.1002/hpja.277
|View full text |Cite
|
Sign up to set email alerts
|

Family violence knowledge in culturally diverse communities and organisational preparedness to disseminate information

Abstract: Issue addressed: Family violence presents a significant threat to the physical and psychological health of individuals and communities, with women from culturally diverse groups experiencing an increased risk of exposure to family violence and barriers to accessing support. It is necessary to examine the knowledge of family violence among these communities and their preferred source of knowledge to facilitate successful family violence prevention strategies.Methods: Thirty-one women (19 Indian and 12 Burmese) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, observations of help-seeking behaviors among non-Anglo-Saxon communities are varied. A systematic review of cross-cultural differences in help-seeking by Satyen et al (2019) found that although Latina/ Hispanic and African American women were less likely to engage in formal help-seeking than Caucasian women overall, they were more likely to utilize primary health care and law enforcement services. These findings indicate that differences in help-seeking may be better understood in the context of the types of formal support sought, rather than the frequency (Flicker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, observations of help-seeking behaviors among non-Anglo-Saxon communities are varied. A systematic review of cross-cultural differences in help-seeking by Satyen et al (2019) found that although Latina/ Hispanic and African American women were less likely to engage in formal help-seeking than Caucasian women overall, they were more likely to utilize primary health care and law enforcement services. These findings indicate that differences in help-seeking may be better understood in the context of the types of formal support sought, rather than the frequency (Flicker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%